Air variation in SOE: Stack experimental study. (28th June 2018) - Barelli, L.; Bidini, G.; Cinti, G.
Abstract: Solid oxide electrolyzer are the electrolysis technology that can achieve higher efficiency and power densities. This study aims to analyze the role of air when used as a sweep gas in the oxygen electrode of a SOE. Based on experimental activity on a SOE stack, both polarization and constant utilization tests were performed changing the air flow rate in the stack. Due to air reduction, oxygen concentration of off gasses was increased from 25% up to 50%. All experimental results indicated that, reducing air flow down to 9% of nominal value, the effect on performances is negligible and variation of voltage is maintained below 2%. Thermoneutral condition was achieved at 500 mA cm −2 . Advantages of air reduction in SOE operation stand in both capital and operation costs. System design is simplified, ancillary consumptions are reduced and, in view of oxygen as a by-product, high oxygen concentrated off gases are produced with lower energy request for possible O2 separation. Highlights: A SOE short stack was tested varying the air flow in the oxygen electrode. Polarization curves and RU curves were performed reducing air flow. Reduction of performances was negligible once flow is reduced down to 9%.